Construct-Specific and Timing-Specific Aspects of the Home Environment for Children’s School Readiness - King, Yemimah A.; Duncan, Robert J.; Posada, German; Purpura, David J. (Frontiers in Psychology, 2020)
Prior evidence supports that the home environment is related to children’s development of school readiness skills. However, it remains unclear how construct- and timing-specific aspects of the home environment are related to children’s school readiness skills, unique from overall, stable aspects of home quality. Unpacking associations due to specific constructs and timing of the home environment may provide insights on the theoretical processes that connect the home environment to school readiness. Using data from the NICHD Study of Early Child Care and Youth Development (N = 1,364), the current study examines how timing (36 and 54 months) and constructs (educational stimulation and socio-emotional responsivity) of the home environment, relative to overall levels across time, relate to children’s language skills, math skills, and externalizing behaviors. The overall, stable aspects of the home environment were significantly associated with children’s language skills and externalizing problems. Additionally, there were significant paths from the stimulation construct at 54 months to math skills, language skills, and externalizing problems. These findings provide evidence that although the overall home environment is predictive of school readiness, the stimulation construct of the home environment at 54 months has additional concurrent relations to children’s school readiness. Implications for the role of the home environment and children’s school readiness are discussed.